Representation Of Masculinity In The Character Dallas In The Film Below Her Mouth (Roland Barthes' Semiotic Analysis) - Oky Dirgantara Angkasa; Nurseri Hasnah Nasution, M.Ag (Tabayyun: Journal of Journalism, 2023)
Abstract In this concept, men are synonymous with violence, active, aggressive, logical, ambitious and strong. This research was conducted to find out the meaning of semiotics regarding the nature of masculinity in the character Dallas contained in the film Below Her Mouth and to analyze what signs are contained in the film Below Her Mouth relating to the nature of masculinity from the signification into two stages or usually called the two orders of signification, namely the study of (Denotation) Denotation and (Connotation) Connotation, is a concept of Barthes's thought. The data collection techniques used were documentation studies, literature studies and online data searches. Researchers draw conclusions that almost all codes represent masculinity in the film Below Her Mouth. The codes that appear such as code of appearance, expression and setting or background have an important meaning in this film as a representation of the nature of masculinity. Other codes, such as costumes, shooting techniques, gestures, make-up, lighting and so on, function as a support to show the value of masculinity that is highlighted in the character of Dallas. Keywords: Below Her Mouth, Masculinity, Representation, Roland Barthes Semiotics